Evitare il significante. Gilles Deleuze e il linguaggio dei segni - Cantone, Damiano (Scenari, 2024)
The essay explores the conception of language in the works of Gilles Deleuze, with particular attention to his rejection of structuralist semiotics and his emphasis on the concept of expression. Through the works of Spinoza, Hjelmslev, and Proust, Deleuze develops a theory of language as an immanent and productive system of signs, opposing the reduction of meaning to linguistic signification. In his later work with Félix Guattari, Deleuze deepens this vision, criticizing structuralist semiology and promoting an immanent semiotics that considers language as matter in continuous differentiation. It is in his works on cinema that he further elaborates, also drawing on the proposals of Pasolini, the idea of language as immanent to matter.